Innovations in Microfinance in Southeast Asia - Gilberto M. Llanto; Ryu Fukui (Philippine Institute for Development Studies (PIDS), 2003)
This paper describes some emerging innovations in microfinance observed in Southeast Asian microfinance markets that make it possible for microfinance institutions (MFIs) to reach a greater number of poor households on a sustainable basis. It discusses the nature, importance and types of innovations. Innovations help reduce the MFI's transaction costs and risks. They also make it possible for poor households to satisfy their investment and consumption smoothing requirements. The paper draws some lessons from the experience with innovations and makes a case for government's important role in ensuring the proper functioning of markets. It points out government's pivotal role in system innovation because of the likelihood of its under-or-slow production by the private sector. MFIs have a clear advantage in process and product innovation to meet the requirements of poor clients. Thus, they should be given room in doing this.
Keywords: 330; microfinance; investment; innovation; policy and regulatory environment; consumption smoothing; Finanzprodukt; Südostasien; Mikrofinanzierung